POLYMORPHISM OF INHIBIN A GENE AND ITS RELATIONSHIP WITH LITTER SIZE IN CHINESE INDIGENOUS GOAT - Q. Y. Liu; Y. Q. He; Y. Ge; M. X. Chu1; M. Jin; Y. J. Zhang; J. Y. Wang; X. K. Ma; R. Di; D. W. Huang; N. Li (Journal of Animal and Plant Sciences, 2017)
Inhibin A (INHA) is a glycoprotein hormone which has a role in regulating the synthesis and secretion of pituitary follicle-stimulating hormone. In this paper, single nucleotide polymorphisms of 5′ regulatory region and exon 1 of INHA gene were detected in one prolific goat breed (Jining Grey goat) and five low to medium fecundity breeds (Boer, Liaoning Cashmere, Wendeng Dairy, Taihang and Inner Mongolia Cashmere goats) by PCR-SSCP and sequencing methods. Its effects on litter size in Jining Grey goats were analyzed. Concerning primer P2, two genotypes (AA and Aa) were detected in Jining Grey, Liaoning Cashmere, Wendeng Dairy and Taihang goats. Sequencing revealed a G→A transition at the 258th position of the amplified region in the genotype AA in comparison to the genotype Aa. For primer P4, two genotypes (BB and Bb) were identified in six goat breeds tested. Sequencing revealed a G→A transition at the 759th position of the amplified region in the genotype BB compared with Bb. Jining Grey goat does with genotype Bb had 0.79 (P<0.01) kids more than those with genotype BB. These results preliminarily showed that G841A of the INHA gene was a potential marker for improving litter size in goats.
Keywords: goat; INHA gene; prolificacy; PCR-SSCP